Neurological Manifestations of HIV-AIDS at Tertiary Care Hospital Quetta - Panezai, Shahrukh; Muhammad Shoaib; Khoso, Noor Ahmed; Panezai, Mahrukh; Essa, Syed Muhammad; Kakar, Sana Ullah (Indus Journal of Bioscience Research, 2024)
Background: HIV and AIDS continue to pose substantial global health challenges, particularly in resource-constrained settings like Pakistan. This study investigated the prevalence and types of neurological manifestations among HIV-AIDS patients treated at a tertiary care hospital in Quetta. Methodology: A cross-sectional analysis was conducted on 200 HIV-AIDS patients using questionnaires, medical records, and laboratory findings. Results: Neurological manifestations were observed in 70% of the patients, with peripheral neuropathy (40%) being the most common condition, followed by HIV-associated neurocognitive disorders (30%), progressive multifocal leukoencephalopathy (10%), cryptococcal meningitis (7.5%), and cerebral toxoplasmosis (5%). Key risk factors included low CD4 counts (<200), advanced HIV stage (AIDS), and the absence of antiretroviral therapy (ART). Findings: These findings underscore the critical need for early diagnosis and intervention in managing the neurological complications of HIV-AIDS. Peripheral neuropathy and cognitive disorders, in particular, highlight the importance of integrating neurological assessment into routine care for HIV patients. The results call for strengthened ART programs, improved access to healthcare resources, and a holistic approach to treatment. Conclusion: Effective management of HIV-AIDS requires a multidisciplinary strategy to address not only the viral infection but also its neurological and systemic complications. Enhancing healthcare infrastructure and awareness is essential to improve outcomes for patients with HIV-AIDS and to reduce the burden of neurological disorders associated with the disease.